Nanocrystal-reinforced soy protein films and their application as active packaging - González, Agustín (2015)
Soy protein isolate (SPI) films reinforced with starch nanocrystals (SNC) were developed by simple casting method. The films were transparent and homogeneous. The opacity and degree of crystallinity increased with the amount of nanocrystals. Moisture content, total soluble matter and Swelling in water were evaluated, showing a marked effect on SNC Additions. As the amount of SNC increased, the films exhibited lower affinity for water. Moreover, mechanical properties were determined showing that SPISNC reinforced films became more resistant and less elongable as SNC amount increased. With the incorporation of a considerable amount of reinforcements, a marked variation was observed in these properties. In addition, assays performed demonstrated that b-Cyclodextrins (b-CD)-containing SPI-SNC films were able to sequester cholesterol when brought into contact with cholesterol rich food such as milk. This effect was more marked as the amount of b-CD into the films increased. The methodologies developed in this work allowed yielding biodegradable films with optimized physical and mechanical properties which were assayed as active food coating.